2021
DOI: 10.1186/s12884-021-03654-3
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical procedure to select intrauterine and extrauterine factors for methodological validation of preterm birth risk estimation

Abstract: Background Etiopathogenesis of preterm birth (PTB) is multifactorial, with a universe of risk factors interplaying between the mother and the environment. It is of utmost importance to identify the most informative factors in order to estimate the degree of PTB risk and trace an individualized profile. The aims of the present study were: 1) to identify all acknowledged risk factors for PTB and to select the most informative ones for defining an accurate model of risk prediction; 2) to verify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 122 publications
(38 reference statements)
1
36
0
Order By: Relevance
“…This drives the impetus for dimensionality reduction and/or feature selection, which can reduce the risk of overfitting, reduce computational resources required for analysis and, in the case of supervised feature selection, can identify the most important features for prediction. A recent study identified intra- and extra-uterine factors most informative of sPTB to estimate risk of sPTB using a random forest classifier with high predictive performance (AUC 0.81) [ 99 ]. The etiology of sPTB is multi-factorial, and is likely driven by more complex, subtle interactions which machine learning approaches, along with feature selection for identifying informative features, is well suited to detect.…”
Section: Discussionmentioning
confidence: 99%
“…This drives the impetus for dimensionality reduction and/or feature selection, which can reduce the risk of overfitting, reduce computational resources required for analysis and, in the case of supervised feature selection, can identify the most important features for prediction. A recent study identified intra- and extra-uterine factors most informative of sPTB to estimate risk of sPTB using a random forest classifier with high predictive performance (AUC 0.81) [ 99 ]. The etiology of sPTB is multi-factorial, and is likely driven by more complex, subtle interactions which machine learning approaches, along with feature selection for identifying informative features, is well suited to detect.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of fundal height is susceptible to measurement personnel, which may limit its clinical use. Della Rosa et al used 9 most informative predictors to build a preterm birth prediction model, and the AUC of the model reached 0.812 [ 35 ]. Our results show that using only 15 predictions can achieve better model predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Risk in the individual after treatment might depend on if other risk factors for PTD also are present. Spontaneous PTD is a multifactorial condition, and only a comprehensive model including major risk factors may present adequate risk estimation for a specific patient [ 43 ]. We suggest that future models for individual prediction of spontaneous PTD include cone-length in the excised specimen, together with other risk factors for PTD.…”
Section: Discussionmentioning
confidence: 99%